Editors of Special Issue - of Special Issue, Editors (Journal of Science and Technology, 2017)
Editors Special Issue of Journal of Science and Technology Issue on the Application of Science and Mathematics Editor In Chief Dr. Suzi Salwah Binti Jikan Universiti Tun Hussein Onn Malaysia Editors Assoc. Prof. Dr. Kavikumar S/O Jacob Universiti Tun Hussein Onn Malaysia Dr. Phang Chang Universiti Tun Hussein Onn Malaysia Dr. Norhayati Binti Muhammad Universiti Tun Hussein Onn Malaysia Dr. Hazel Monica Matias-Peralta Universiti Tun Hussein Onn Malaysia Dr. Nurun Najwa Binti Ruslan Universiti Tun Hussein Onn Malaysia Dr. Maria Elena Binti Nor Universiti Tun Hussein Onn Malaysia Dr. Norazlin Binti Abdullah Universiti Tun Hussein Onn Malaysia Dr. Amira Saryati Binti Ameruddin Universiti Tun Hussein Onn Malaysia Dr. Saliza Binti Asman Universiti Tun Hussein Onn Malaysia Dr. Shakila Binti Abdullah Universiti Tun Hussein Onn Malaysia Dr. Nurul Nadia Binti Adnan Universiti Tun Hussein Onn Malaysia